“White Trash” in Literary History: The Social Interventions of Erskine Caldwell and James Agee - Holtman, Janet (American Studies, 2018)
This article proceeds from the assertion that most literary scholars dismiss these American authors of the early twentieth century due to aesthetic or social valuations that do not fully take into account what might be gained from an interdisciplinary engagement with their works as social discourse. It then covers some of the historical insights that may be gained from examining their socially engaged texts of the thirties and outlines some of the cultural theoretical lenses that might be most useful in gleaning such insights. Finally, it suggests that the works of Caldwell and Agee are important for understanding both a specific cultural moment and the more general formative impact it has had on current cultural perceptions and modes of scholarly engagement with the rural poor.